The Accelerator in Income Analysis: Reply - Tsiang, S. C. (Quarterly Journal of Economics, 1952)
Journal Article The Accelerator in Income Analysis: Reply Get access S. C. Tsiang S. C. Tsiang International Monetary Fund Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 66, Issue 4, November 1952, Pages 596–599, https://doi.org/10.2307/1882109 Published: 01 November 1952